A composite nanostructured electron-transport layer for stable hole-conductor free perovskite solar cells: design and characterization. Issue 11 (2nd March 2016) - Yu, Zhenhua; Qi, Fei; Liu, Pei; You, Sujian; Kondamareddy, Kiran Kumar; Wang, Changlei; Cheng, Nian; Bai, Sihang; Liu, Wei; Guo, Shishang; Zhao, Xing-zhong
Abstract : A novel composite nanostructured titanium dioxide (TiO2 ) based electron-transport layer (ETL) is designed by combining size blended nanoparticles (SBNP) and nanoarrays (NA) for efficient perovskite solar cell (PSC). Abstract : A novel composite nanostructured titanium dioxide (TiO2 ) based electron-transport layer (ETL) is designed by combining size blended nanoparticles (SBNP) and nanoarrays (NA) for efficient perovskite solar cell (PSC) applications. The composite nanostructured (SBNP + NA) ETL is successfully employed in hole-conductor free PSCs, there by achieving a stable device with a maximum efficiency of 13.5%. The improvement in the performance is attributed to the better charge transport and lower recombination in the SBNP + NA ETL. Despite the stable high efficiency, SBNP + NA ETL based PSCs are advantageous owing to their low cost, ease of all-solution fabrication process in an open environment and good reproducibility.